Nuevos registros de aves en el noroeste argentino - Di Giacomo , Alejandro G.; Di Giacomo, Adrián S.; López Lanús, Bernabé M.; Caradonna, Ángel (El Hornero, 1995)
Este artículo no cuenta con un resumen.